Profitability Ratio Analysis to Measure the Financial Performance of PT. Fajar Benua Indopack Medan Branch During and After the COVID- 19 Pandemic - Tengku Narasiya Adiza; Rahima Br Purba; Noviani Noviani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study analyzed profitability ratios as indicators of the financial performance of PT. Fajar Benua Indopack Medan Branch during and after the COVID‑19 pandemic. The method used was a descriptive-analytical quantitative approach with a longitudinal case study covering the period 2020–2024. The variables analyzed included Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results showed a significant decline in all three ratios during the pandemic due to operational disruptions, market demand fluctuations, and increased costs; however, the post-pandemic period indicated gradual recovery. These findings highlighted the importance of asset and capital management, as well as adaptive operational strategies to face external pressures. The profitability ratio analysis provided a comprehensive overview of operational efficiency, crisis response, and the company’s readiness during the recovery phase. This study provided a basis for management to plan strategically, make data-driven decisions, and improve sustainable profitability in the future.